A low-frequency study of recently identified double-double radio galaxies. Issue 4 (15th May 2019) - Nandi, S; Saikia, D J; Roy, R; Dabhade, P; Wadadekar, Y; Larsson, J; Baes, M; Chandola, H C; Singh, M
ABSTRACT: In order to understand the possible mechanisms of recurrent jet activity in radio galaxies and quasars, which are still unclear, we have identified such sources with a large range of linear sizes (220–917 kpc), and hence timescales of episodic activity. Here we present high-sensitivity 607-MHz Giant Metrewave Radio Telescope (GMRT) images of 21 possible double-double radio galaxies (DDRGs) identified from the FIRST survey to confirm their episodic nature. These GMRT observations show that none of the inner compact components suspected to be hotspots of the inner doubles are cores having a flat radio spectrum, confirming the episodic nature of these radio sources. We have identified a new DDRG with a candidate quasar, and have estimated the upper spectral age limits for eight sources which showed marginal evidence of steepening at higher frequencies. The estimated age limits (11–52 Myr) are smaller than those of the large-sized (∼1 Mpc) DDRGs.